Developing Interactive Electronic Book Based on TPACK to Increase Creative Thinking Skill - Budi Halomoan Siregar; Kairuddin Kairuddin; Abil Mansyur (STAI Hubbulwathan Duri, 2021)
This study aims to: (1) improve the creative thinking skills of prospective teachers, (2) measure the level of validity, practicality, and effectiveness of the developed electronic book. This type of research is research and development (RD) by applying the ADDIE model. This research was conducted through 5 stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The subjects of this study were students (prospective teachers) in the 5th-semester consisting of 55 people in the IT-based learning media course. At the same time, the object of this research was an electronic book developed based on TPACK. Several instruments were used: observation sheets, questionnaires, validation sheets, and essay tests. The results of data analysis indicate that the electronic book has met the requirements of validity, practicality, and effectiveness. In addition, there was a significant increase in the ability to think creatively.